Biomedical Sleep Inducer System - Mahanta, Deepjyoti; Bordoloi, Hemashree; Saikia, Samar Jyoti (Journal of Science & Technology, 2021)
Sleeping difficulty called insomnia, can involve difficulty in falling asleep one who has first go to bed at night, waking up too early in the morning and waking up often during night. The lack of restful sleep can affect your ability to hold out daily responsibilities. All types of insomnia can cause day time drowsiness, poor concentration, and therefore the inability to feel refreshed and rested in the morning. Magnetic flux related to the plannet is termed geo-magnetic fields. It is essentially dipolar on the earth’s surface. Many of us experience sleeping well within the natural surroundings into a tent or a wooden hut. This fact is because of not only to the healthy atmosphere but also from our unconscious ability to perceive natural earth’s magnetic fields. Our paper is about this sort of geo-magnetic –fields. This has been designed a circuit, which radiates an electromagnetic field which is low frequency through a radiator coil and our aim is to perceive them, in this manner our brain is surrounded by a perfect environment for a sound sleep.